A REVIEW OF SOME FACTORS AFFECTING THE ACCURACY OF MEASURING THE GEOMETRIC CHARACTERISTICS OF MORTISE AND TENON JOINTS (Innovation in Woodworking Industry and Engineering design, 2026)
The geometric characteristics of mortise and tenon joints represent their ideal shape as well as the permitted deviations from that shape. Measurement accuracy as part of production metrology is of crucial importance for maintaining tolerances and fits as well as quality control in production. The closeness of the measurement results to the actual true value of the measurand depends on many factors. Some factors that affect the accuracy of a measurement are caused by the measuring equipment, the environment in which the measurement is performed, the operator who performs the measurement, the method and procedure of the measurement and the properties of the material.This review paper presents an investigation of the factors and their affect on the accuracy of measurement of mortise and tenon joints while maintaining manufacturing tolerances. The purpose of this investigation is to consider the possibility of their minimization to obtain a more accurate measurement.According to the theoretical analysis, the group of factors that express the heterogeneity and hygroscopicity of wood as a material have a great effect on the accuracy of the measurement.